Asuhan Kebidanan Continuity of Care (COC) pada Ny. N G1P0A0 Umur 20 Tahun - Muspitarini; Rini Susanti (Universitas Ngudi Waluyo, 2025)
Based on World Health Organization data, the Maternal Mortality Rate (MMR) in the world in 2020 was 223/100,000 per live birth and in Indonesia in 2021 the Maternal Mortality Rate (MMR) was 7,389 cases per 100,000 live births. Efforts to reduce the Maternal Mortality Rate (MMR) are carried out through the provision of quality and sustainable health services, starting from pregnancy, childbirth, postpartum, neonates, to the selection of contraceptives. Continuity of Care in midwifery is a series of continuous and comprehensive service activities starting from pregnancy, childbirth, postpartum, newborn care and family planning services. The purpose of the study was to be able to provide comprehensive midwifery care to Mrs. N aged 20 years starting from pregnancy, childbirth, postpartum, newborns and Family Planning. The research method is a case study. The collection technique was obtained using secondary and primary data. Primary data was obtained through interviews, observations, and examinations. Secondary data was obtained through the KIA book and the results of supporting examinations. Documentation uses the assessment format according to Varney's 7-step Midwifery Care and SOAP. The case study was conducted on January 9, 2025 to May 17, 2025. Research results In Mrs.